Relationship of Student Learning Creativity With SBdP Learning Outcomes Grade Iv Sd Gpid Palu - Erlis Erlis; Yun Ratna Lagandesa (Universitas Tadulako, 2022)
The purpose of this study is to find out the relationship of student learning creativity with the learning outcomes of SBdP Class IV SD GPID Palu. The hypothesis tested in this study is